2019
DOI: 10.3390/agronomy9110709
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis and Gene Mapping for a Short-Petiole Mutant in Soybean (Glycine max (L.) Merr.)

Abstract: Short petiole is a valuable trait for the improvement of plant canopy of ideotypes with high yield. Here, we identified a soybean mutant line derived short petiole (dsp) with extremely short petiole in the field, which is obviously different from most short-petiole lines identified previously. Genetic analysis on 941 F2 individuals and subsequent segregation analysis of 184 F2:3 and 172 F3:4 families revealed that the dsp mutant was controlled by two recessive genes, named as dsp1 and dsp2. Map-based cloning s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…A característica com maior c.v. foi produtividade, isso pode ser explicado, pois a produtividade é uma característica governada por muitos genes e recebe forte influência ambiental. Em relação à produtividade, estudos apontam que a seleção de variedades de soja com alta produtividade está associada a características como maior número de vagens e maior número de grãos por vagem (Kaur et al, 2018;Li et al, 2019). No presente estudo, os tratamentos Check e Elite apresentaram as maiores produtividades, o que pode estar relacionado a essas características.…”
Section: Resultados E Discussõesunclassified
“…A característica com maior c.v. foi produtividade, isso pode ser explicado, pois a produtividade é uma característica governada por muitos genes e recebe forte influência ambiental. Em relação à produtividade, estudos apontam que a seleção de variedades de soja com alta produtividade está associada a características como maior número de vagens e maior número de grãos por vagem (Kaur et al, 2018;Li et al, 2019). No presente estudo, os tratamentos Check e Elite apresentaram as maiores produtividades, o que pode estar relacionado a essas características.…”
Section: Resultados E Discussõesunclassified
“…The short petiole mutant VP5 was identified from a fast neutron-induced mutant population, and the phenotype of the VP5 mutant was co-segregated with an 837,919 bp deletion fragment on chromosome 17 [ 45 ]. Moreover, the derived short petiole ( dsp ) mutant was controlled by two recessive genes, dsp1 and dsp2 , which were mapped on chromosome seven with flanking markers BARCSOYSSR_07_0787 and BARCSOYSSR_07_0808 and on chromosome 11 between markers BARCSOYSSR_11_0037 and BARCSOYSSR_11_0043, respectively [ 46 ]. Recently, Wang et al [ 47 ] found that the rolled leaves and short petioles mutant ( rlsp1 ) was controlled by multiple genes, and identified 10 candidate regions on chromosomes three, six, eight, thirteen, and seventeen using sequencing-based bulked segregant analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using soybean breeding line SS98206SP determined that the short petiole trait is controlled by lps3 located in a 12 cM region between markers Sat_234 and Sct_033 in linkage group F (chromosome 13) [7]. Moreover, Liu et al (2019) mapped two recessive loci, dsp1 and dsp2, underlying the short-petiole phenotype to two nonhomologous regions of chromosome 7 and chromosome 11, respectively; 36 and 33 genes were predicted within the physical genomic interval of dsp1 and dsp2, respectively [12].…”
Section: Introductionmentioning
confidence: 99%